Pisang Emas dan Social Movement Menuju Industri Kreatif : (Analisis Potensi di Desa Sumber Tangkil Kecamatan Tirtoyudo Kabupaten Malang) - M. Romli Muar; A.Fahrur Rozi; Sagita Martha Triyani (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2020)
Sumber Tangkil Village, Tirtoyudi District, Malang Regency, East Java is one of the villages that has abundant natural wealth, among its natural wealth There are many golden banana trees found. In this area the Golden Banana is a source of eyes the life of the local community in fulfilling their daily needs, will but the golden bananas that are abundantly don't get the maximum treatment not even accepted in the market. This research was conducted using qualitative descriptive research method. The results and benefits that can be drawn from this research are: maximizing the natural potential possessed by conducting coaching society through changes in social movements towards actions and mindsets productive and innovative based on the role of the community in improving the level of the economy Public